Ferramentas e metodologia para consolidação de dados de usinas hidreletricas brasileiras - Hidalgo, Ieda Geriberto, 1976- (2009)
Orientadores: Secundino Soares Filho, João Eduardo Gonçalves Lopes, Marcelo Augusto Cicogna